Alternatives to cow's milk products in infant nutrition: Goat's milk-based formulas - Kamil Hozyasz (Kazimierz Wielki University, 2017)
There is increasing consumer awareness of the relationship between nutrition and health. Goat milk is a food of high nutrition value, with high biological value protein, and a good source of minerals and medium chain fatty acids. Infant formula manufacturers nowdays offer a wide range of products based on cow's milk and non-bovine milks, trying to fulfill the needs of young children. The review discusses the key factors influencing the market demand for goat's milk products.